2019
DOI: 10.1038/s41598-019-46639-1
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Thymosin Alpha-1 Does Not Influence F508del-CFTR Maturation and Activity

Abstract: Deletion of phenylalanine 508 (F508del) in the cystic fibrosis transmembrane conductance regulator (CFTR) anion channel is the most frequent mutation causing cystic fibrosis (CF). F508del-CFTR is misfolded and prematurely degraded. Recently thymosin a-1 (Tα-1) was proposed as a single molecule-based therapy for CF, improving both F508del-CFTR maturation and function by restoring defective autophagy. However, three independent laboratories failed to reproduce these results. Lack of reproducibility has been ascr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Both cysteamine and thymosin a-1 were also claimed to restore functional expression of F508del-CFTR (Tosco et al, 2016;Romani et al, 2017). Nevertheless, several independent CF research groups failed to demonstrate rescue of F508del-CFTR PM expression and function by either cysteamine or thymosin a-1 (Tomati et al, 2018b;Armirotti et al, 2019;Awatade et al, 2019). Although the immunomodulatory effect of these molecules in CF remains to be further exploited, they did not demonstrate F508del-CFTR correction.…”
Section: Identifying Feasible Solutions For a Cf Healthcare Cost Sustmentioning
confidence: 99%
“…Both cysteamine and thymosin a-1 were also claimed to restore functional expression of F508del-CFTR (Tosco et al, 2016;Romani et al, 2017). Nevertheless, several independent CF research groups failed to demonstrate rescue of F508del-CFTR PM expression and function by either cysteamine or thymosin a-1 (Tomati et al, 2018b;Armirotti et al, 2019;Awatade et al, 2019). Although the immunomodulatory effect of these molecules in CF remains to be further exploited, they did not demonstrate F508del-CFTR correction.…”
Section: Identifying Feasible Solutions For a Cf Healthcare Cost Sustmentioning
confidence: 99%
“…In that context, cysteamine, approved for the treatment of cystinosis [ 207 ], was tested in CF mice, followed by a small open-label clinical trial in PwCF, where it was shown to reduce sweat chloride levels in F508del carrying PwCF, but not in a cohort which contained PwCF carrying two non-F508del mutations not responsive to current CFTR modulators [ 208 , 209 ]. More recently, however, functional rescue by cysteamine and thymosin α1—the rescue by the latter also reported to occur through promoting autophagy [ 210 ]—could not be confirmed by several other labs [ 211 , 212 , 213 ], dampening the enthusiasm to stimulate autophagy as a way of reversing the CF phenotype.…”
Section: Cftr Causal Therapiesmentioning
confidence: 99%
“…Interestingly, the study also showed that Tα1 was capable of increasing CFTR maturation, stability, and activity [54,55]. Nevertheless, this latter effect was not confirmed by subsequent studies [56,57]. More recently, the group of Romani and colleagues suggested that Tα1 can also have beneficial effects in CF extrapulmonary pathology.…”
Section: Thymosin Alpha-1mentioning
confidence: 98%